2018
DOI: 10.1371/journal.pone.0194186
|View full text |Cite
|
Sign up to set email alerts
|

Congenital cytomegalovirus, parvovirus and enterovirus infection in Mozambican newborns at birth: A cross-sectional survey

Abstract: BackgroundCongenital cytomegalovirus (cCMV) infection is the most prevalent congenital infection acquired worldwide, with higher incidence in developing countries and among HIV-exposed children. Less is known regarding vertical transmission of parvovirus B19 (B19V) and enterovirus (EV). We aimed to assess the prevalence of CMV, B19V and EV vertical transmission and compare results of screening of congenital CMV obtained from two different specimens in a semirural Mozambican maternity.MethodsA cross sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(15 citation statements)
references
References 66 publications
0
14
1
Order By: Relevance
“…Other studies show that transmission rates for primary infections can be as high as 78%, with the rate increasing with gestational age, as it can range from 30.1% transmission in the first trimester to 72.2% in the third trimester [49,50]. These high transmission rates in women who are acutely infected are in stark contrast to the low birth prevalence in seropositive populations found from our systematic review, which ranged from 0.4% to 6% [19,26,27,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], despite expected high CMV exposure rate in these populations. This range mirrors work by Fowler et al, (2003) in whichupon comparing primary versus non-primary maternal CMV infections they found that 3% of infants were infected by primary maternal infection versus 1% by non-primary maternal infection [34].…”
Section: Discussionmentioning
confidence: 52%
See 2 more Smart Citations
“…Other studies show that transmission rates for primary infections can be as high as 78%, with the rate increasing with gestational age, as it can range from 30.1% transmission in the first trimester to 72.2% in the third trimester [49,50]. These high transmission rates in women who are acutely infected are in stark contrast to the low birth prevalence in seropositive populations found from our systematic review, which ranged from 0.4% to 6% [19,26,27,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], despite expected high CMV exposure rate in these populations. This range mirrors work by Fowler et al, (2003) in whichupon comparing primary versus non-primary maternal CMV infections they found that 3% of infants were infected by primary maternal infection versus 1% by non-primary maternal infection [34].…”
Section: Discussionmentioning
confidence: 52%
“…Of those, 16 studies reported symptoms of affected infants. Overall, cCMV birth prevalence ranged from 0.4% to 6% [19,26,27,[29][30][31][32][33][34][35][36][37][38][39][40][41][42][43]. Tier 1 studies, which differentiated primary versus chronic CMV maternal infections, had a median birth prevalence rate of 1%.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[ 2 ] Congenital symptomatic CMV infection is characterized by intrauterine growth restriction; hepatosplenomegaly, hematological abnormalities like anemia, thrombocytopenia, pneumonitis, and gastrointestinal tract disease. [ 3 ] Treatment of CMV retinitis is usually done with systemic (oral/intravenous) or intravitreal ganciclovir. Untreated retinitis can progress to blindness because of extensive retinal necrosis, optic nerve involvement, or retinal detachment.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, CMV was four-fold more prevalent among HIV-infected infants compared with uninfected infants born to HIV-infected mothers not receiving antiretrovirals during pregnancy. On the contrary, a cross-sectional Mozambican survey showed no differences in the prevalence of CMV infection among HIV-exposed and unexposed neonates [ 98 ]. Unfortunately, there is still a lack of preventive approaches and behavioural procedures for CMV infection during pregnancy.…”
Section: Reviewmentioning
confidence: 99%